PENGEMBANGAN RUMAH SAKIT UMUM DAERAH KUBU RAYA DARI KELAS D MENJADI KELAS C - Mamuraja, Gabriella Flavia; Alhamdani, Muhammad Ridha; Lubis, Mira Sophia (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
A hospital is a healthcare institution that provides comprehensive individual healthcare services, offering inpatient, outpatient, and emergency care. In Indonesia, the development of hospitals has been significant, particularly in Kubu Raya Regency situated in the West Kalimantan Province. Kubu Raya is the youngest regency in West Kalimantan, formed from the division of Pontianak Regency. Within its healthcare facilities, Kubu Raya has three public hospitals, one of which is RSUD Kubu Raya categorized as type/class D. Considering the population growth and its distance from the city center of Pontianak, the upgrading of RSUD Kubu Raya from class D to C represents the government's effort to enhance healthcare quality for the community by providing more comprehensive and reliable medical facilities, infrastructure, and personnel.